Diagnostic Accuracy of Specific IgE Against Wheat and Rye in Flour-Induced Occupational Asthma - Doyen, Virginie; Migueres, Nicolas; Frère, Alexandra; Walusiak-Skorupa, Jolanta; Wiszniewska, Marta; Suojalehto, Hille; Munoz, Xavier; Romero-Mesones, Christian; van Kampen, Vera; Sastre, Joaquin; Quirce, Santiago; Barranco, Pilar; et al. (The journal of allergy and clinical immunology in practice (Cambridge, MA), 2024)
Assessment of IgE-mediated sensitization to flour allergens is widely used to investigate flour-induced occupational asthma. The diagnostic efficiency of detecting specific IgE antibodies (sIgEs) against wheat and rye flour, however, has not been thoroughly compared with other diagnostic procedures. We sought to evaluate the diagnostic accuracy of sIgE against wheat and rye compared with specific inhalation challenge (SIC) with flour as the reference standard. This retrospective multicenter study included 264 subjects who completed an SIC with flour in eight tertiary centers, of whom 205 subjects showed a positive SIC result. Compared with SIC, sIgE levels of 0.35 kU /L or greater against wheat and rye provided similar sensitivities (84% to 85%, respectively), specificities (71% to 78%), positive predictive values (91% to 93%), and negative predictive values (56% to 61%). Increasing the threshold sIgE value to 5.10 kU /L for wheat and to 6.20 kU /L for rye provided a specificity of 95% or greater and further enhanced the positive predictive value to 98%. Among subjects with a positive SIC, those who failed to demonstrate sIgE against wheat and rye (n = 26) had significantly lower total serum IgE level and blood and sputum eosinophil counts and a lesser increase in postchallenge FeNO compared with subjects with a detectable sIgE. High levels of sIgE against wheat and/or rye flour strongly support a diagnosis of flour-induced occupational asthma without the need to perform an SIC. The absence of detectable sIgE against wheat and rye in subjects with a positive SIC seems to be associated with lower levels of T 2 biomarkers.